Effect of hydrothermal aging on the properties of zirconia with different levels of translucency - Amarante, José Eduardo Vasconcellos (2020)
Objectives: The aim of this study was to evaluate the effect of hydrothermal aging on the mechanical properties and translucency of dental zirconia with different levels of translucency. Methods: Three different types of dental yttria-stabilized zirconia were used: 3Y-TZP (ZrO2 - 3 mol.% Y2O3) of medium opacity (designated Z3OP), 3Y-TZP of medium translucency (Z3MT), and 5Y-PSZ (ZrO2 - 5 mol.% Y2O3) of high translucency (Z5HT). A total of 120 specimens were sintered (n = 40 specimens/group). The control group (sintered→polished→heat-treated) and the aged group (sintered→polished→heat-treated→hydrothermally degraded at 134 °C, 2 bar, 5h) were characterized by relative density, quantitative phase analysis by X-ray diffraction using the Rietveld method, microstructural analysis by scanning electron microscopy, surface roughness and translucency. All groups were submitted to a biaxial flexural strength test. Data analysis using Kruskal-Wallis, Nemenyi (p-value = 0.05), and Weibull statistics were used. Results: All sintered specimens presented full densification. After aging, an increase of the m-ZrO2 phase content was observed for the Z3OP group. On the other hand, Z3MT and Z5HT did not show any m-ZrO2 phase, indicating resistance to the hydrothermal degradation. Smaller grains were observed in the Z3MT group in relation to Z3OP group and the Z5HT group presented a bimodal grain distribution, where the largest grains were associated to cubic ZrO2. Z3OP exhibited a slight increase in roughness as a function of degradation, while the roughness remained statistically stable in the other groups. Translucency was little influenced by degradation, but considerably affected by increasing thickness. The Z5HT samples were the group with the highest translucency among the control groups. Z3OP exhibited the highest flexural strength, while being the most susceptible to hydrothermal degradation. The lowest values were presented by Z5HT in all groups, due to the high concentration of c-ZrO2 grains. Conclusion: Hydrothermal aging is less critical to the flexural strength of zirconia-based materials than the materials’ composition and microstructure. Z5HT zirconia showed the highest translucency, however the measured difference is not visually perceptible. Z5HT was considered the most resistant to hydrothermal degradation.